THE IMPLEMENTATION OF ICT (PADLETE) IN LEARNING ENGLISH IN WRITING SKILLS - Haryudin, Acep; Resmana, Iqbal Fatwa (P2M STKIP Siliwangi, 2020)
It is an undeniable fact that most of our students nowadays can enjoy having new technology either at homes or at schools. For this, it is quite possible for them to have ICT for learning. The purpose of having this kind of method is that students will have two advantages at the same time, i.e. the linguistic aspects and the content. For the linguistic aspects, firstly, they will learn the English sound system through spelling, secondly the grammar, by combining words into longer utterances, and finally the choice of words or vocabulary. While for the content, ICT let the students learn (assisted by the teacher) the variety of language used within a certain subject. Teaching technique using chalk and talk or explanation is not popular anymore. It is then suggested that the teacher uses internet within his teaching learning process and it is also compulsory for the students to learn to use it. The Internet is a must, because it can be used (1) as the source of knowledge (2) as an aid for learning (instructional aid) (3) as teaching or learning facility (4) as a standard of competency (5) as an administrative equipment (6) as a supporting equipment for the school management (7) as an educational infrastructure. Beside the aforementioned aspects, there are additional factors to consider. Among others are (a) the environmental factor which consists of school or institution holding the activity (b) students who learn, their ages, social and economical background, the language and literacy of IT, the variety of learning (c) the teacher, consists of the background of the teacher, the age, the teaching style, the experience and the personality (d) factors of technology which consists of computer, software, internet network and other application of EducateNet at schools. This research was conducted at one of the MTS in Cimahi who had applied ICT / Padlet in the learning process. The research method was CAR / Classroom Action Research, the results obtained by using one of the ICT Media, so that learning was interesting, interactive, not transportation and students became languages English is easier.Â